Rancangan Pembelajaran Berkarakteristik Pembelajaran Inovatif Abad 21 pada Materi Teks Deskriptif dengan Model Pembelajaran Problem Based Learning di Smp Negeri 1 Talang - Uyub, Moh (Universitas Pancasakti Tegal, 2022)
Writing scientific articles aims to describe the steps in using problem-based solving methods in learning to write descriptive texts so that they can improve students' abilities in the intended learning. The problem in this writing is how the steps for using problem-based solving methods in learning to write descriptive texts are. To solve the problem and the purpose of writing, a descriptive method is used with a library study data collection method. The results of the writing provide an overview of the steps in using problem-based solving methods in learning to write descriptive text, beginning with student orientation to problems, organizing students for learning, guiding individual and group investigations, developing and presenting students' work and finally analyzing and evaluating the process. solution to problem. From the results of this writing, it can be concluded that the use of problem-based solving methods in learning to write descriptive texts for students makes it possible to develop students' thinking skills. Meanwhile, educators demand to be able to fully understand each and every concept of the teaching and learning process. The problem-based learning model emphasizes the problem-solving process, involving students in active, collaborative, student-centered learning to face increasingly complex challenges.